The Influence of English Language Film Media on Students English Language Skills - Felim Alzena Nandhita; Adri Fernando Oktoriyadi; Rachel Mutiara Nisa; Hera Hera; Pani Ade Wijaya; Verawati Verawati (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: In today's era of globalization, English has become a crucial means of communication in various fields such as education, technology, and international relations. Consequently, the demand for effective and engaging English language learning methods continues to grow. One supplementary learning method that is gaining popularity is the use of English-language films. Films provide exposure to authentic language use, including vocabulary, grammar, pronunciation, intonation, and cultural elements not always available in textbooks. Through repeated exposure to dialogue and visual context, learners can improve their listening comprehension, speaking fluency, and overall language awareness. Aim: The purpose of this study was to analyze the extent to which English-language film media influences learners' speaking skills. Method: This study is a bibliometric study conducted by analyzing scientific articles published between 2020 and 2025 using the Google Scholar database. The analysis process was carried out using software to visualize relationships between keywords, research trends, and author collaborations. Results and Dıscussion: The results of the study indicate that there are twelve dominant keywords grouped into two main categories. The keyword "film" emerged as a central term in the first group, closely related to the keywords "learning media," "students," and "skills," indicating its role as a learning tool. Meanwhile, the second group is dominated by the keywords "English," "influence," and "skills," reflecting the research focus on the impact of film media on English language proficiency. The total strength of the associations of 326 and 61 keyword relationships indicate a high level of thematic relevance among the analyzed studies.